2002
DOI: 10.1117/12.454765
|View full text |Cite
|
Sign up to set email alerts
|

<title>Bacterial paleontology for astrobiology</title>

Abstract: We review the development ofBacterial Paleontology and consider its relevance ofthe rapidly emerging field of Astrobiology. We present electron microscopic images of fossil bacteria in different states of preservation in Earth rocks and Astromaterials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…А всего лишь через 10 лет описано уже более 100 минералов, образование которых может быть связано с деятельностью микроорганизмов [6,7]. Некоторые минералы, например магнетит, могут образовываться внутри клеток магнитотактичных бактерий; фосфатные и другие минералы могут откладываться как снаружи, так и внутри клеток [23]. Результаты изучения ископаемых бактерий показывают, что минералообразование под влиянием бактерий или с их участием -это процесс, который появился на Земле вместе с возникновением бактерий [22].…”
Section: биогенные минералы псевдоморфозы в микроорганизмах в метеорunclassified
“…А всего лишь через 10 лет описано уже более 100 минералов, образование которых может быть связано с деятельностью микроорганизмов [6,7]. Некоторые минералы, например магнетит, могут образовываться внутри клеток магнитотактичных бактерий; фосфатные и другие минералы могут откладываться как снаружи, так и внутри клеток [23]. Результаты изучения ископаемых бактерий показывают, что минералообразование под влиянием бактерий или с их участием -это процесс, который появился на Земле вместе с возникновением бактерий [22].…”
Section: биогенные минералы псевдоморфозы в микроорганизмах в метеорunclassified
“…Hoover and co-workers have reported 36,37,38 microbial fossils in meteorites from Mars and from unknown sources. This has added significantly to evidence for extraterrestrial microorganisms in meteorites reported 39 as early as 1961.…”
Section: Introductionmentioning
confidence: 97%
“…When eroded, redeposited and concentrated in other areas of accumulation, bauxite is called sedimentary bauxite. Lateritic bauxites are formed in hot, alternately humid tropical climates, in conditions of relatively calm tectonic regime, and on smooth positive relief forms, in conditions of abundant water exchange and mass development of biota [2]. Lateritic bauxites crown the zonal profiles of the weathering crust.…”
Section: Introductionmentioning
confidence: 99%